THE EFFECT OF USING ENGLISH TALK SHOW VIDEO FOR IMPROVING LISTENING COMPREHENSION AT TENTH GRADE SMA IT FADHILAH PEKANBARU - Rizkiyani, Rizkiyani; Gushendra, Rizky (Journal of English and Arabic Language Teaching, 2025)
This research aimed at finding out the effect of using English talk show video on increasing student listening comprehension at the tenth grade of Islamic Integrated Senior High School of Fadhilah Pekanbaru.  Pre-experimental design was used in this research with one experimental class given a talk show as a treatment.  Data were collected through pretest and posttest with student worksheets compiled based on the indicators of the ability to understand the gist or general overview of the text listened to, the ability to understand main ideas or important information, the ability to understand specific information and remember important details, the ability to understand the speaker attitude or meaning toward the listener or the topic discussed, and the ability to understand implied meaning through inference and deduction from spoken information.  The research findings showed an increase in the mean score from 32.67 in the pretest to 66.67 in the posttest.  Analyzing data with paired sample t-test yielded the score of significance 0.000 (<0.05), so it indicated a significant difference in student listening comprehension between before and after the treatment.  Thus, it could be concluded that there was a significant effect of using talk show video on increasing student listening comprehension.  This research recommended the use of talk show video as an effective and enjoyable learning medium in English learning at Senior High School level.